Survival and growth of Silicon Valley high-tech businesses born in 2000. - Luo, Tian; Mann, Amar (Monthly Labor Review, 2011)
High-tech businesses born in 2000 in the Silicon Valley had below-average survival and employment growth rates from 2000 to 2009, except for the year 2000, during which surviving firms of the cohort experienced significant growth that carried over for 8 years; year-specific and industry-mix effects, however, weaken the latter conclusion